PHILOSOPHY AS A SYSTEM OF CONDITIONALS - Nieznański, Edward (Studia Philosophiae Christianae, 2020)
Philosophical statements are often suppositions. Gottfried Wilhelm Leibniz proposes in Nouveaux Essais sur l’entendement humain, 1704, a method of the construction of assertive conditionals occurring between any philosophical suppositions. If we can infer a philosophical statement from any suppositions then the implication between these suppositions and the obtained statement is assertive. In the article, some examples of the application of Leibniz’s method are considered.